PERENCANAAN PARTISIPATIF DALAM PENYUSUNAN RENCANA DETAIL TATA RUANG KOTA WAISAI, RAJA AMPAT, PAPUA - Yuniartanti, Rizki Kirana (REKSABUMI, 2022)
One of the Government's National Development Priority agendas in the National Medium-TermDevelopment Plan (RPJMN) 2020-2024 is developing regions to reduce inequality and ensure equity.This effort is carried out through the preparation of a Detailed Spatial Plan (RDTR). RDTR as areference for submitting confirmation/approval of of the Suitability of Spatial Utilization Activities(KKPR) which can be carried out according to the level of risk according to the standards and qualityof space or environment. The Waisai Urban Area, Raja Ampat Regency, West Papua Province is oneof the areas that urgently needs to accelerate the preparation of the RDTR due to the large investmentopportunities there, especially the tourism sector.Preparation of the Detailed Spatial Plan for the Waisai Urban Area by applying the participatoryplanning concept. This is because the community is the beneficiary of the preparation of the DetailedSpatial Plan for the Waisai Urban Area. This research will describe the preparing process that applies the concept of participatory planning. Then in this study will also assess the level of communityparticipation in each activity of discussion forums and public consultations which are carried out usinga combined research approach (mixed method research) and scoring analysis tools. This researchwill assess the level of community involvement in the preparation of the RDTR, as well as the realcontribution of community involvement. This research can be an example of learning for thepreparation of RDTR in Raja Ampat Regency in particular and other regions in Indonesia in generalby applying the concept of community participation.